Stink Bug Population in Cotton Plantations with Different Plant Spacings - Izidro dos Santos de Lima Júnior (Revista Agrogeoambiental, 2020)
The increase in cotton plant population by decreasing the spacing between rows cause some changes in phenotypical characteristics of cotton plants, such as decrease in number of leaves per plant, low-development leaves, and great soil shading. Stink bugs of the Pentatomidae family that migrate from soybean crops seem to benefit from the cotton narrow-row planting system. The objective of the present work was to evaluate adult and nymph stink bug populations in cotton plantations under three plant spacing. The experiment was conducted in the 2010/2011 cotton season at the Experimental Farm of the Federal University of Grande Dourados, in Dourados, MS, Brazil. A randomized block experimental design was used, with three cotton growing systems and eight replications, totaling 24 plots. The cotton growing systems were selected based on spacing between planting rows (0.22, 0.45, and 0.90 m). Five evaluations were conducted to survey the stink bug populations, with two samples per plot. The number of nymphs and adults of Euschistus heros and Edessa meditabunda was counted. The spacing between cotton planting rows affects stink bug populations of the species Euschistus heros and Edessa meditabunda. Increases in cotton plant density decrease the occurrence of stink bug in the plantation. The stink bug population is greater in cotton plantations with spacing of 0.90 m between planting rows.